1982
DOI: 10.1007/bf00052766
|View full text |Cite
|
Sign up to set email alerts
|

Biological spectrum and other structural functional attributes of the vegetation of Kumaun Himalaya

Abstract: Spectra on life form, leaf size, leaf persistence, flowering season, and shade tolerance of trees in different vegetation types occurring within the north-western catchment of the river Gola in Kumaun Himalaya are presented. The flora of Quercus leucotrichophora, Quercus lanuginosa and Quercusfloribunda forests is phanerophytic, that of Pinus roxburghii and mixed forests therophytic. The grassland vegetation is characterized by the largest percentage of hemicryptophytes. The flora of the whole area, is theroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…Therophytes was dominant life form which indicates disturbed environmental conditions in the study area, and biotic pressure on vegetation which increase the short live species. Our findings are in agreement with Saxena et al (2004); Farag (2014) and Ali et al (2016) which show that biotic pressure effect the vegetation. As Costa et al (2007) reported that therophytes are dominant life form in South Eastern Brazil which is similar to our finding.…”
Section: Discussionsupporting
confidence: 94%
“…Therophytes was dominant life form which indicates disturbed environmental conditions in the study area, and biotic pressure on vegetation which increase the short live species. Our findings are in agreement with Saxena et al (2004); Farag (2014) and Ali et al (2016) which show that biotic pressure effect the vegetation. As Costa et al (2007) reported that therophytes are dominant life form in South Eastern Brazil which is similar to our finding.…”
Section: Discussionsupporting
confidence: 94%
“…The dominant therophytes, chamaephytes, and cryptophytes altogether constituted 49.1% of the life forms proportion. Therophytes showed the maximum divergence of the normal spectrum; other workers had also reported a similar phytoclimatic association for different tracks of vegetation [38,12,32,39]. The dominance of therophytes (71 species, 25.63%) indicates that the investigated area was under mild biotic pressure.…”
Section: Life Form and Biological Spectrumsupporting
confidence: 54%
“…Climatic types may be characterized by the prevailing plant life forms in the plant communities under a specific climatic regime [9][10][11][12]. The biological spectra of the Indian region are related to specific edaphic, altitudinal and climatic factors [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Saxena et aL (1982) concluded that along the major altitudinal gradient (from tropical to alpine), the phenerophytes decrease in importance, hemicryptophytes increase and chamaephytes, cryptophytes and therophytes do not show much alteration. Meher Homji (1964) concluded that the life forms of different regions of the country are reflected by the bio-climate of the area.…”
Section: Discussionmentioning
confidence: 99%